The cause and effect of fall from height accidents and mitigation measures in Peninsular Malaysia - Mat Salleh, Mohamad Ariff (2022)
Falls from height (FFH) is a significant threat to the construction environment and are the leading cause of serious and fatal injuries for construction workers in Peninsular Malaysia and throughout the world. Working at a height increases the likelihood of being involved in a fall from a height accident. Many previous researches or most current incident investigation protocols concentrate on immediate accident circumstances rather than exploring how the problems originate, the effect of accidents and how to mitigate the accidents, often due to the need to prosecute offenders or limitations in time and resources for the investigation. This research is motivated to identify the cause and effect of fall from height accidents and its mitigation measures in Peninsular Malaysia. The quantitative approach was adopted in identifying the cause, effect and mitigation measures of fall from height accidents. A questionnaire survey has been used as the main method in the data collection and was distributed to 365 respondents around Peninsular Malaysia. But, only 115 set questionnaires were returned completely. Data were analysed using the Relative Important Index (RII). The findings of this research indicate that the main causes of fall from height accidents are individual attitudes, which are workers' negligence toward safety rules with an RII value of 0.901. Then, the adverse effects of falls from height accidents are in humanitarian categories, which are injuries, or permanent disabilities with an RII value of 0.899. After that, the utmost possible mitigation measures with the highest RII ranking are in the health protection categories, which are forbid working at height if alcohol or drugs have been detected on workers with an RII value of 0.930. Lastly, the identified causes, effects and mitigation measures of fall from height accidents were selected and integrated into a framework of fall from height accidents, which are a novelty for this research. The establishment of the framework is important to recognise the root cause of the problem and enhance safety performance at site.